Review Pemikiran Moderat Para Tokoh Islam dalam Buku Pendidikan Agama Islam dan Budi Pekerti - Lilik Huriyah; Hammis Syafaq; Nasihatul Latifah (Islamica: Jurnal Studi Keislaman, 2020)
Nowadays, moderate Islamic thought has been emphasized by the Indonesian government. This can be seen from the school curriculum that includes moderate Islamic thought and tolerance. This study seeks to review moderate Islamic thinking that was initiated by Islamic reformers in the book Pendidikan Agama Islam (PAI) dan Budi Pekerti of class XI Senior High School, that was published by the Ministry of Education and Culture in 2014 and 2017. This article used library research. All data is collected through documentation and analyzed using content analysis. The results of this study stated that in the 2014 edition of the PAI dan Budi Pekerti class XI there was one Islamic figure whose thoughts were extreme and did not include moderate, namely Muh}ammad b. ‘Abd al-Wahhāb. So that in the 2017 edition of PAI dan Budi Pekerti class XI, the figure of ‘Abd al-Wahhāb is no longer presented and replaced with a moderate-minded Islamic figure, namely Namik Kemal. The nine other Islamic figures have moderate Islamic thoughts both in the 2014 and 2017 book edtions.